Soil quality index assessment for conventional, organic and INM based rice cropping systems using key indicators as influenced by imbalanced fertilization - Theresa, K.; Vijayakumar, S.; Muthukrishnan, R.; Raja, Vigneshwaran (Frontiers in Environmental Science, 2026)
IntroductionImbalanced fertilization in rice ecosystems disrupts nutrient equilibrium between soil replenishment and crop uptake, leading to reduced yield and soil degradation. Sustainable alternatives such as organic and Integrated Nutrient Management (INM) practices are increasingly evaluated for their potential to enhance soil quality and productivity.MethodsA four-season study compared conventional farming (CF), organic farming (OF), and INM practices in rice systems. Principal Component Analysis (PCA) was used to eliminate multicollinearity and derive relative weights (Wi) for selected soil indicators (Si) to compute the soil quality index (SQI). Key biological and chemical indicators—phosphatase activity (PA), water-holding capacity (WHC), soil microbial biomass carbon (SMB-C), organic carbon (OC), zinc (Zn), and urease activity (UA)—were measured.ResultsCF fields recorded lower SQI values compared with organic and INM systems. Organic and INM fields exhibited higher SQI values of 0.99 and 0.88, respectively. Within CF treatments, a super-optimal nitrogen dose (250%) resulted in the lowest SQI (0.573) and yield (3.20 t ha−1), while the 125% N treatment (CF6) achieved the highest SQI (0.715) and yield (6.20 t ha−1). Super-optimal phosphorus and potassium levels generally reduced yield except in CF6.Discussion/ConclusionIntegrating soil physical, chemical, and biological properties through a weighted additive index (WAI) method effectively established the link between soil quality and function. Optimizing fertilizer doses rather than maximizing them can improve both soil quality and rice productivity, offering a sustainable pathway for managing nutrient dynamics in intensive rice ecosystems.